2005
DOI: 10.1007/s00109-005-0684-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and genotyping studies implicate the interleukin 7 receptor in the pathogenesis of primary progressive multiple sclerosis

Abstract: Multiple sclerosis (MS) is an enigmatic disease of the central nervous system resulting in sclerotic plaques with the pathological hallmarks of demyelination and axonal damage, which can be directly or indirectly orchestrated by cells from the peripheral circulation. The majority of patients with MS follow a relapsing-remitting course in the early stages of the disease (RRMS) but most ultimately enter a secondary progressive phase (SPMS). About 10% of patients follow a primary progressive course from the onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
69
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 40 publications
7
69
1
2
Order By: Relevance
“…[25][26][27][28][29][30][31] We recently demonstrated by using a multivariable model that IL-7Ra haplotype-2 was a significant predictor of more rapid CD4 T-cell recovery following suppressive cART in an Australian-based largely Caucasian HIVinfected cohort. 22 Consistent with observations in haplotype-2 carriers in HIV-uninfected cohorts, 9,11,32,33 we found that HIV-infected patients who were homozygous for haplotype-2 had significantly lower concentrations of sIL-7Ra compared with non-haplotype-2 carriers. 22 We therefore proposed that the reduced sIL-7Ra levels in haplotype-2 carriers may increase the availability of IL-7 to bind to membrane-bound IL-7Ra on T-cells, leading to faster CD4 T-cell recovery.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…[25][26][27][28][29][30][31] We recently demonstrated by using a multivariable model that IL-7Ra haplotype-2 was a significant predictor of more rapid CD4 T-cell recovery following suppressive cART in an Australian-based largely Caucasian HIVinfected cohort. 22 Consistent with observations in haplotype-2 carriers in HIV-uninfected cohorts, 9,11,32,33 we found that HIV-infected patients who were homozygous for haplotype-2 had significantly lower concentrations of sIL-7Ra compared with non-haplotype-2 carriers. 22 We therefore proposed that the reduced sIL-7Ra levels in haplotype-2 carriers may increase the availability of IL-7 to bind to membrane-bound IL-7Ra on T-cells, leading to faster CD4 T-cell recovery.…”
Section: Introductionsupporting
confidence: 88%
“…This association has been shown previously in Caucasian cohorts, 11,22 and rs6897932 is thought to be the functional SNP altering the splicing and production of soluble IL7Ra. 9,32 Our findings are the first description of a significant association between sIL-7Ra levels and the SNP at rs6897932 in Africans.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Our study replicates previous reports of association between IL7R variants with PrMS, emphasizing the existence of specific genetic components implicated in the development of progressive disease. [11,21] Sequencing of IL7R in MS patients identified two missense variants (rs6897932, p.T244I and rs3194051, p.I356V) with an allelic frequency difference greater than 8% from those expected in the general population ( Table 2). The p.T244I variant, genotyped in this study, has been shown to affect alternative splicing of IL7R exon 6 and alter the amounts of soluble and membranebound protein, thus suggesting a possible mechanism for disease.…”
Section: Discussionmentioning
confidence: 99%
“…The p.T244I variant, genotyped in this study, has been shown to affect alternative splicing of IL7R exon 6 and alter the amounts of soluble and membranebound protein, thus suggesting a possible mechanism for disease. [6,21] In contrast, no functional outcome has been described for p.I356V, and association studies for this variant (rs3194051) have provided conflicting results, with some studies reporting significant association with risk of MS, [22][23][24] that others could not replicate. [6,25] In summary, our study has confirmed the association between genetic variants in IL2RA and IL7R in MS, and further defined this association to specific disease subtypes.…”
Section: Discussionmentioning
confidence: 99%